CONCEPTUAL DESIGN AND FEASIBILITY ANALYSES OF ROBOTIC SYSTEM FOR AUTOMATED PIGGING OPERATION - ABDUL RAHMAN, MOHD SYAFIQ (2011)
PIGGING TECHNOLOGY DISCOVERED AND DEVELOPED ORIGINALLY BY THE OIL INDUSTRY MORE THAN 100 YEARS AGO. THE TERM PIGGING IS PRIMARILY ASSOCIATED WITH CLEANING. THE OBJECTIVE OF THIS PROJECT IS TO DESIGN A PIG LAUNCHER ROBOT THAT CAN ASSIST IN PIG LAUNCHING TASK WHICH REQUIRES NO HUMAN INTERVENTION AND REDUCE OPERATION TIME DURING PIGGING PROCESS.